If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -5n = 0 Reorder the terms: -5n + 2y = 0 Solving -5n + 2y = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2y' to each side of the equation. -5n + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 -5n + 0 = 0 + -2y -5n = 0 + -2y Remove the zero: -5n = -2y Divide each side by '-5'. n = 0.4y Simplifying n = 0.4y
| 24+8x=-96 | | -4K+3=-13 | | 10x+61=-59 | | 5.25+b=22.75 | | 8x+16=100 | | 40-6x=-116 | | g(x)=1482 | | 0.5x*10=0.15 | | 14n^2/2n^2 | | -5(x-6)=-34+3x | | 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 | | 5n-n=15+7 | | 7x-x=-16-2x | | -7r-8-5r=-13-7r | | 9x+45=100 | | f(x)=(x^7-4x^6)*(x+3)*(x-2) | | 9x+36=100 | | 12+3m=7m-2m | | 8x+32=100 | | v+4=-12+1-v-1 | | 10=4-5n+4n | | 7x+28=100 | | 7x+21=100 | | 2x-3-6x=-7x-6 |